(3LdGA GdZTjGf Yf ebdI GdEfSGfs - (3YKeGf Hf SfO GdfLOj GdHUQj, HOQ GdOjf, GHf SfO , J (B1242 (3g` s; (3GHf SfO GdHUQj , YKeGf Hf SfO GdfLOj, HOQ GdOjf,J (B1242 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi hGaQ JaVdg hHYO ajbhd YKeGf Hf SfO Efi deG fXeJ efXheJi ebdI GdEfSGf hMdI GdYGOi ef GdHjGf ai Led GdfMh GdeMdGI HYbhO GdEYQGH Cf CTQMgG HTQM jMd ef CdaGXgG SejJg LdGA GdZTjGf s
(3BNQgG (B:s
(3jbhd ajfaP eG jbhd JMGUQhG HgPG GdeKGHI Hchfge YOh dG HELeGY fGaPi GdCbhGd QVi Gddg Yfge hCfG CUdi hCSde Ydi CTQa GdSGOI GdeQSdjf eMeO hYdi Bdg hUMHg GdejGejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B367s
Keywords: (3GdfMhs